Um estudo sobre trabalho e educação das crianças no setor de jóias e bijuterias em Limeira - Locali, Tammy Ticiane (2011)
Child labor has been often presented to society through family labor, being that, in the city of Limeira, it gained repercussion after the publication of the dissertation written by Marcos Antonio Libardi Ferreira (2005) entitled 'Estudos de risco à saúde do trabalhador e ao meio ambiente na produção de joias e bijuterias em Limeira-SP', which denounced the existence of six thousand children between the ages of eleven and sixteen years old working in the sector. This situation has showed itself recurrent, mainly in families which have found themselves obligated to assign services to their children, so they can raise funds and meet at least their basic necessities. The investigation project 'Um estudo sobre a atividade das crianças no setor de joias e bijuterias em Limeira', aims to fill an existent gap in the educational area, due to the fact that there are not researches referring to the theme in the sector of semi-jewels in Limeira, county which is considered the Brazilian capital of veneers and being few the jobs which give emphasis to the symbolic, cultural and historical aspects of this type of research. In order to answer the leading questions, this work is based on a whole theoretical structure, coming from a literary background about the subject and having a more empirical character which will be verified by questionnaires with formal and informal questions, clarifying how the process of production of the pieces is given, besides semi-structured interviews with students from Emeief Professora Maria Apparecida de Luca Moore, located at the Parque Residencial Aeroporto in Limeira, school that assists children who work with semi-jewels inside their homes, in order to verify their labor conditions, searching for gathering as much information as possible about these conditions and the consequences of this labor inside and outside the classroom.